PERBANDINGAN SISTEM PENDIDIKAN NEGARA JEPANG DAN INDONESIA - Adek Nilasari Harahap; Azwar Ananda; Nurhizrah Gistituati; Rusdinal Rusdinal; Tinur Rahmawati (JURNAL EDUCATION AND DEVELOPMENT, 2024)
Indonesia and Japan have different education systems. The Japanese and Indonesian education systems each have unique advantages and disadvantages. Indonesia is currently ranked 72 out of 77 countries, Indonesia's education system needs greater attention. There are many education experts born in Indonesia who can improve the education system in Indonesia. Indonesia's education system is moving on the right track. Comparing Indonesia with countries that have strong education systems, such as Japan, is one strategy to move the Indonesian education system in the right direction. with countries that have strong educational institutions, such as Japan. Children in Japan are taught moral principles, politeness, and discipline starting from the age of 0 to 4. Children in Japan who have reached the fourth grade of elementary school have to take exams that are not too tough for other students. Exams that are not too burdensome for students. The Japanese education system has a lot to offer Indonesia.